Advances in the Mechanism and Applications of Stimulus-responsive DNA Hydrogels - He, Yifan; Huang, Zhaohe; Pei, Xiaojing; Dong, Yinmao; Yang, Xiangliang (Current Pharmaceutical Biotechnology, 2025)
DNA hydrogels possess numerous unique and attractive features, including excellent biocompatibility and biodegradability, as well as inherent programmability, catalytic functionality, therapeutic potential, and precise molecular recognition and bonding capabilities. Furthermore, intelligent DNA hydrogels exhibit stimuli-responsive behaviors, transitioning between gel and sol states in response to various stimuli, including pH, temperature, enzymes, and others. Through intelligent, rational design and controlled preparation of DNA nanostructures, a broad spectrum of advanced applications has been realized. In this mini-review, we focus on recent developments in the construction strategies, molecular structures, and functional mechanisms of DNA hydrogels. Additionally, representative applications of stimuli-responsive DNA hydrogels are discussed. Finally, challenges and the future outlook of DNA hydrogels are proposed.
Keywords: hydrogels